Plasma YKL‐40: a potential biomarker for psoriatic arthritis?. (23rd May 2012) - Jensen, P.; Wiell, C.; Milting, K.; Poggenborg, R.P.; Østergaard, M.; Johansen, J.S.; Skov, L.
Abstract Background Plasma YKL‐40 is an inflammatory biomarker. No useful biomarker exists in patients with psoriasis or psoriatic arthritis. Objective To measure YKL‐40 and high‐sensitivity C‐reactive protein (hs‐CRP) in patients with psoriasis or psoriatic arthritis before and during treatment. Methods In 48 patients with psoriasis, we measured YKL‐40, hs‐CRP and Psoriasis Area and Severity Index (PASI) at inclusion and in a subgroup of 14 patients, we repeated the measurements after four to six weeks of methotrexate treatment. In 42 patients with psoriatic arthritis, we measured YKL‐40 and hs‐CRP at inclusion and during 48 weeks of adalimumab treatment. The patients with psoriatic arthritis were divided into responders and non‐responders. Results In patients with psoriasis, the baseline median PASI score was 10.8 and baseline YKL‐40 was 45 μg/L. Seventeen per cent had elevated plasma YKL‐40 compared with healthy subjects. Baseline PASI and YKL‐40 were not correlated (rho = 0.14, P = 0.347) and YKL‐40 and hs‐CRP remained unchanged after treatment. In patients with psoriatic arthritis, the median pretreatment YKL‐40 was 112 μg/L and 43% had elevated YKL‐40. YKL‐40 decreased in 33 patients who responded to adalimumab (from 112 μg/L to 68 at 48 weeks, P = 0.007). Hs‐CRP decreased (from 4.65 mg/L to 0.91, P = 0.013) in the responders. In the non‐responders (n = 9), YKL‐40 and hs‐CRP remained unchanged. Conclusions YKL‐40 is elevated in many patients with psoriatic arthritis, but not in patients with psoriasis. YKL‐40 decreased in patients with psoriatic arthritis who responded to treatment. YKL‐40 may be a useful biomarker to monitor the effect of treatment with tumour necrosis factor‐α inhibitors in patients with psoriatic arthritis.